0
$\begingroup$

if $f(x) = x^5+ x^3 + x$, then $f^{-1}(3) = ?$

I TRIED to do it, and I got this answer : 3/91 . I don't know if it is correct or not?

I tried to do this work like this: $$ y = x^5+x^3+x\\ y = x(x^4+x^2+1)\\ y/(x^4+x^2+1) = x\\ y = x/(x^4+x^2+1)\\ f^{-1}(x)= x/(x^4+x^2+1)\\ f^{-1}(3)=3/91$$

$\endgroup$
  • 4
    $\begingroup$ What is $f(1)$? Also notice that $f'(x)\gt0$. $\endgroup$ – robjohn Feb 7 at 22:41
  • $\begingroup$ Your fourth step is wrong. You go from $\frac{y}{x^4+x^2+1} = x$ to $y = \frac{x}{x^4+x^2+1}$, i.e., moved the denominator from one side to the other; you would have had to multiply through by $x^4+x^2+1$, and that would just have given you back your second line. $\endgroup$ – Arturo Magidin Feb 7 at 22:50
  • $\begingroup$ @ArturoMagidin how would i do it then? $\endgroup$ – Sports Highlights Feb 7 at 22:53
  • $\begingroup$ P.S. You'll have a very hard time finding an analytic formula for $f^{-1}$. But you aren't supposed to find one. You can use calculus to verify that $f$ is one-to-one, and then eyeball a number that $f$ maps to $3$, to get the value of $f^{-1}(3)$. You don't need to figure out how to invert every value, just $3$. $\endgroup$ – Arturo Magidin Feb 7 at 22:54
1
$\begingroup$

Let $y=y(x)$ is an inverse function.

Thus, $y^5+y^3+y=3,$ which since $y^5+y^3+y$ increases, gives $y=1$ and $f^{-1}(3)=1.$

$\endgroup$
  • $\begingroup$ How are your $y$ and $f$ (or $f^{-1}$) related to $x$ and $f$ from the original post? $\endgroup$ – Wolfgang Kais Feb 8 at 10:31
  • $\begingroup$ I just used the definition of inversed functions. You can see it in the net or I'll come back to the home and I'll write this definition. $\endgroup$ – Michael Rozenberg Feb 8 at 10:42
  • $\begingroup$ Thank you. Maybe it's just $y=f^{-1}(3)$ and thus $3=f(f^{-1}(3))=f(y)=y^5+y^3+y$... I think that I missed that one step. $\endgroup$ – Wolfgang Kais Feb 8 at 12:02
  • $\begingroup$ @Wolfgang Kais Indeed, $f(f^{-1}(3))=3$ because for all $x$ from the domain of $f^{-1}$ we have $f(f^{-1}(x))=x$, but $f^{-1}(3)=f^{-1}(f(1))=1.$ $\endgroup$ – Michael Rozenberg Feb 8 at 12:29
  • $\begingroup$ Thanks, but that's clear. The step missing in my mind was that you replaced $x$ from the definition of $f(x)$ with $y=f^{-1}(3)$, the desired value. The confusing thing was that you were looking at the problem from the $y$-axis (assuming that we already have an inverse function and solving an equation concerning the image of $f^{-1}$) while all other answerers (including me) solved an equation of the form $f(x)=3$, looking at the problem from the $x$-axis. :-) $\endgroup$ – Wolfgang Kais Feb 8 at 13:38
1
$\begingroup$

$f(x)-3 = x^5+x^3+x-3 = (x-1)(x^4+x^3+2x^2+2x+3) = 0$ $\Leftrightarrow x=1 \quad \lor \quad x^4+x^3+2x^2+2x+3 = 0$

Since $f'(x) = 5x^4 + 3x^2 + 1 \ge 1 > 0$ for all $x \in \mathbb R$, $f$ is strictly monotone increasing, thus $x=1$ must be the only (real) solution.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.